Longitudinal Assessment of Gut Microbiome Alterations in Early Childhood and Their Impact on Neurodevelopmental Outcomes - MHM, Nazmul; Aung, Thidar; Myint Htoo, Phone; Shwe, Wana Hla; C, Priyanka; RN, Jegathambigai; Madhu, Sandra Rumi; Y, Farzana; Doustjalali, Saeid Reza; Sabet, Negar Shafiei; Hosseini, Hoorieh Sadat; Oo, Khin Thane; et al. (Journal of Neonatal Surgery, 2025)
This longitudinal study investigates the dynamic evolution of the gut microbiome in early childhood and its relationship with neurodevelopmental outcomes across cognitive, motor, and behavioral domains. A cohort of 196 children was followed from birth to five years, with quarterly stool samples analyzed via 16S rRNA sequencing and standardized neurodevelopmental assessments conducted annually. Results revealed that children with delayed colonization of Bacteroides and Faecalibacterium exhibited lower cognitive and language scores, while higher microbial diversity was consistently associated with improved executive functioning. Predictive modeling identified specific microbial taxa—such as Veillonella, Blautia, and Ruminococcus—as strong early-life indicators of later neurodevelopmental performance (AUC = 0.86). These findings emphasize the mechanistic role of the gut-brain axis in early human development and suggest that microbiome-informed pediatric interventions may offer a viable strategy to enhance neurodevelopmental health.